2016
DOI: 10.1177/1359105316676333
|View full text |Cite
|
Sign up to set email alerts
|

Depression among left-behind children in China

Abstract: By retrieving literature published from 2005 to 2015 from Chinese National Knowledge Infrastructure, Wanfang, Vip, PubMed, and Web of Science, we filtered out studies using the Children's Depression Inventory only and compared left-behind children and non-left-behind children. The methodological quality of the papers was evaluated using the Newcastle-Ottawa Scale. Finally, we included six studies to carry out a meta-analysis. The results showed that the Children's Depression Inventory scores of left-behind chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Left-behind children involve the children who are under 18 years and are left at home when both or one of their parents migrate to urban areas to work for at least six months 2. While it is well documented that left-behind children in rural China are disadvantaged in terms of psychosocial and academic functioning,3,4 there are still some gaps in the literature: (1) whether early left-behind experiences are linked to psychosocial functioning in later life, especially for emerging adulthood; (2) extensive studies focus on negative outcomes of left-behind populations,5 however, how about the positive psychosocial functioning of this vulnerable group; and (3) little is known about the protective factors for psychosocial adjustment in this vulnerable group.…”
Section: Introductionmentioning
confidence: 99%
“…Left-behind children involve the children who are under 18 years and are left at home when both or one of their parents migrate to urban areas to work for at least six months 2. While it is well documented that left-behind children in rural China are disadvantaged in terms of psychosocial and academic functioning,3,4 there are still some gaps in the literature: (1) whether early left-behind experiences are linked to psychosocial functioning in later life, especially for emerging adulthood; (2) extensive studies focus on negative outcomes of left-behind populations,5 however, how about the positive psychosocial functioning of this vulnerable group; and (3) little is known about the protective factors for psychosocial adjustment in this vulnerable group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared to non-left-behind children (NLBC), the long separation from parents will put LBC into an even more vulnerable situation. Therefore, in recent years, concerns regarding to the health status of LBC have been accumulated [57].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from previous investigations indicated that left‐behind children were at high risks for psychological and mental disorders (e.g., Shen, Liu, Zhao, & Shi, ). Left‐behind children reported more psychopathological outcomes than general children, including depression (Liang, Wang, & Rui, ), anxiety (Liu, Li, & Ge, ), and suicide ideation (Fu et al, ). It was estimated that approximately 30% of the left‐behind children experienced mental health problems (Liang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Left‐behind children reported more psychopathological outcomes than general children, including depression (Liang, Wang, & Rui, ), anxiety (Liu, Li, & Ge, ), and suicide ideation (Fu et al, ). It was estimated that approximately 30% of the left‐behind children experienced mental health problems (Liang et al, ). The lack of parent–child communication (Davison & Birch, ) and family care and education (Fan et al, ) has been identified as the important reasons leading to the adverse psychological disorders among left‐behind children.…”
Section: Introductionmentioning
confidence: 99%